2021
DOI: 10.3390/microorganisms9051007
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio Species in an Urban Tropical Estuary: Antimicrobial Susceptibility, Interaction with Environmental Parameters, and Possible Public Health Outcomes

Abstract: The genus Vibrio comprises pathogens ubiquitous to marine environments. This study evaluated the cultivable Vibrio community in the Guanabara Bay (GB), a recreational, yet heavily polluted estuary in Rio de Janeiro, Brazil. Over one year, 66 water samples from three locations along a pollution gradient were investigated. Isolates were identified by MALDI-TOF mass spectrometry, revealing 20 Vibrio species, including several potential pathogens. Antimicrobial susceptibility testing confirmed resistance to aminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 64 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Two of the three Vibrio tested positive for the production of extended spectrum betalactamases which were identified as Vibrio cholerae were positive and this correlated with the findings of Canellas et al [25] who reported that four strains of tested Vibrio cholerae were producers of extended-spectrum beta-lactamases and their antimicrobial susceptibility testing confirmed resistance to aminoglycosides, betalactams (including carbapenems and thirdgeneration cephalosporins), fluoroquinolones, sulfonamides, and tetracyclines. The report also correlates with the findings of Ceccarelli et al [26] whose finding was positive for detection of Vibrio beta-lactamases producers among screened isolates.…”
Section: Discussionsupporting
confidence: 84%
“…Two of the three Vibrio tested positive for the production of extended spectrum betalactamases which were identified as Vibrio cholerae were positive and this correlated with the findings of Canellas et al [25] who reported that four strains of tested Vibrio cholerae were producers of extended-spectrum beta-lactamases and their antimicrobial susceptibility testing confirmed resistance to aminoglycosides, betalactams (including carbapenems and thirdgeneration cephalosporins), fluoroquinolones, sulfonamides, and tetracyclines. The report also correlates with the findings of Ceccarelli et al [26] whose finding was positive for detection of Vibrio beta-lactamases producers among screened isolates.…”
Section: Discussionsupporting
confidence: 84%
“…Vibrio spp. are indigenous to the sea, and in recent years, the occurrence of resistance genes in several species has been observed [ 6 , 15 ]. Herein, we observed that V. alginolyticus , previously described as a potential pathogen, was the most frequent species with an antibiotic non-susceptibility phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic-resistant Vibrio spp. strains, carrying clinically relevant antibiotic resistance genes (ARGs), have been isolated from marine environments [ 4 , 5 , 6 ]. Sometimes, these bacteria can also harbor virulence genes that increase their pathogenic potential [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections due to Vibrio species are becoming a global public health menace. The species most commonly involved in human infections include; Vibrio cholerae (V. cholerae) and Vibrio parahaemolyticus (V. parahaemolyticus) [15,16].…”
Section: Introductionmentioning
confidence: 99%